Scrotal sonography in early management of subclinical varicocele and male infertility - Rahul Prajapati,; Jigarsingh Jadeja,; Mansukh Patel, (Universiti Kebangsaan Malaysia, 2015)
Background: Varicocele is the most common cause of male infertility. About 20–30% men with varicocele are infertile. The clinically obvious varicocele is identifiable and correctable cause of male infertility, but less is known about the subclinical varicocele and its relationship to infertility. However, subclinical varicocele seems to be an important cause of infertility and hence scrotal ultrasonography is increasingly used in the diagnosis of subclinical varicocele. This study was undertaken to reveal incidence of subclinical varicocele in patients with severely impaired fertility potential. Objectives: To find the prevalence of subclinical varicocele in subjects of severely impaired fertility potential. Materials and Methods: The semen samples were obtained from 31 male partners (age 25–40 years) of infertile couples (sperm count less than 1 million/ml) attending the OPD Smt. SCL Hospital, Ahmedabad. They were analyzed for routine seminogram parameters. In this study, we evaluated male subjects with severely impaired fertility potential using scrotal ultrasonography, follicle-stimulating hormone, luteinizing hormone, and free testosterone. Results: The subclinical varicocele was present in 12 of 31 infertile male subjects evaluated. Percentage prevalence of subclinical varicocele was observed to be 39%. Hormonal levels of all the subjects studied were within normal limit. There was no significant difference in testicular volume of affected side and contralateral side of infertile male subjects. Conclusion: Scrotal ultrasonography is an important technique to reveal the subclinical varicocele for early diagnosis and management of these infertile male subjects.